Physical And Physiological Quality Of Sweet Corn Seeds Of Unpad Hybrid Parental line seed after 2 and 4 Month Storage - Annisa Nur Rahmani; Anne Nuraini, Sumadi, Dedi Ruswandi, Agus Wahyudin (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2018)
Sweet corn is a cultivated plant grown dor fresh consumpption or food industry. The purpose of this study was to examine the physical seed quality and physiological seed quality during storage. The research was conducted in Laboratorium Teknologi Benih Universitas Padjajaran in July 2017 until November 2017. The study consisted of one experiments carried out by using a completely randomized design with two replication using 16 genotypes between Unpad sweet corn seed crossed with released varieties such as Bonanza, Latanza, Sweet boy and Talenta and Unpad sweet corn seed were not crossed with released varieties. Results from this study showed that genotype 533 as the best physical quality in the parameters of 100 grain weight and water content of seed. genotype 871 as the best physical quality in the parameters of germination capacity and seed growth simultaneously. Results from this study also showed that genotype 974 as the lowest physical quality in the parameters of 100 grain weight and water content of seed. genotype 858 as the lowest physical quality in the parameters of germination capacity and seed growth simultaneously.